Prevalence of renal cysts and association with risk factors in a general population: an MRI-based study. - Mensel, Birger; Kühn, Jens-Peter; Kracht, Felix; Völzke, Henry; Lorbeer, Roberto; Lieb, Wolfgang; Dabers, Thomas (Abdominal Radiology, 2018)
Purpose: To assess the prevalence and size of renal cysts and to analyze associated risk factors in a general population using magnetic resonance imaging (MRI).Methods: Data of 2063 participants (1052 women) of the Study of Health in Pomerania who underwent whole-body MRI were included. Renal cyst prevalence was calculated separately for men and women and for 10-year age groups. The association between risk factors and occurrence of renal cysts was estimated.Results: The prevalence of renal cysts was 27% and higher in men (34%) than in women (21%; p < 0.001). Renal cyst prevalence increased from 14% in the youngest age group (20-29 years) to 55% in the oldest age group (≥ 70 years) for men and from 7% to 43% for women (both p < 0.001). In the subset of participants with renal cysts, the total mean number was higher in men (1.9) compared to women (1.6, p = 0.012) and was significantly associated with age. Mean renal cyst size was higher in men (1.50 cm) compared to women (1.18 cm, p < 0.001). Male sex (OR 1.83, 95% CI 1.47; 2.26), older age (OR 1.05, 95% CI 1.04; 1.06, per 1-year increment), and hypertension (OR 1.27, 95% CI 1.00; 1.61) were associated with higher renal cyst prevalence. In additional analyses, current smoking and ex-smoking showed a significantly higher risk for renal cysts (OR 1.47, 95% CI 1.05; 2.05 and OR 1.38, 95% CI 1.04; 1.82, respectively).Conclusions: The prevalence, number, and mean size of renal cysts are higher in men compared to women and are associated with age. In addition, renal cyst prevalence is higher in hypertensive and smoking subjects.